Aging modulates the oscillatory dynamics underlying successful working memory encoding and maintenance. Issue 6 (16th March 2016) - Proskovec, Amy L.; Heinrichs‐Graham, Elizabeth; Wilson, Tony W.
Abstract: Working memory is central to the execution of many daily functions and is typically divided into three phases: encoding, maintenance, and retrieval. While working memory performance has been repeatedly shown to decline with age, less is known regarding the underlying neural processes. We examined age‐related differences in the neural dynamics that serve working memory by recording high‐density magnetoencephalography (MEG) in younger and older adults while they performed a modified, high‐load Sternberg working memory task with letters as stimuli. MEG data were evaluated in the time‐frequency domain and significant oscillatory responses were imaged using a beamformer. A hierarchical regression was performed to investigate whether age moderated the relationship between oscillatory activity and accuracy on the working memory task. Our results indicated that the spatiotemporal dynamics of oscillatory activity in language‐related areas of the left fronto‐temporal cortices were similar across groups. Age‐related differences emerged during early encoding in the right‐hemispheric homologue of Wernicke's area. Slightly later, group differences emerged in the homologue of Broca's area and these persisted throughout memory maintenance. Additionally, occipital alpha activity during maintenance was stronger, occurred earlier, and involved more cortical tissue in older adults. Finally, age significantly moderated the relationship between accuracy and neural activity in the prefrontal cortices. In younger adults, as prefrontal activity decreased, accuracy tended to increase. Our results are consistent with predictions of the compensation‐related utilization of neural circuits hypothesis (CRUNCH). Such differences in the oscillatory dynamics could reflect compensatory mechanisms, which would aid working memory performance in older age. Hum Brain Mapp 37:2348–2361, 2016 . ©2016 Wiley Periodicals, Inc.